2007
DOI: 10.1074/jbc.m703537200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase Activity, Trimerization, and the C-terminal Polybasic Region Are All Required for PRL1-mediated Cell Growth and Migration

Abstract: The phosphatase of regenerating liver (PRL) phosphatases are implicated in a number of tumorigenesis and metastasis processes. The PRLs are unique among protein-tyrosine phosphatases in that they have extremely low phosphatase activity, a high propensity for trimer formation, and a polybasic region that precedes the C-terminal prenylation motif. To investigate the functional significance of these distinctive biochemical and structural features, we established a cell-based system in which ectopic PRL1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(122 citation statements)
references
References 44 publications
(56 reference statements)
6
116
0
Order By: Relevance
“…p115 RhoGAP Negatively Regulates Cell Migration and ERK1/2 and RhoA Activation-It is well documented that PRL-1 promotes cell migration through activation of the ERK1/2 and RhoA pathways (10,11,13,14). It has also been reported that p115 RhoGAP inhibits cell motility through its GAP and C-terminal SH3 domains (31).…”
Section: Structural Basis Of Prl-1 Interaction With Peptide 1 and Thementioning
confidence: 99%
See 2 more Smart Citations
“…p115 RhoGAP Negatively Regulates Cell Migration and ERK1/2 and RhoA Activation-It is well documented that PRL-1 promotes cell migration through activation of the ERK1/2 and RhoA pathways (10,11,13,14). It has also been reported that p115 RhoGAP inhibits cell motility through its GAP and C-terminal SH3 domains (31).…”
Section: Structural Basis Of Prl-1 Interaction With Peptide 1 and Thementioning
confidence: 99%
“…Recent biochemical studies revealed that PRL-1 promotes cell proliferation and invasion by up-regulating both the ERK1/2 and RhoA pathways (10,11,13,14). ERK1 and ERK2 are serine/threonine kinases that are required for many fundamental processes, including cell proliferation, survival, and motility (15), whereas the Rho family GTPases are recognized mainly as key regulators of actin cytoskeletal dynamics and cell migration (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PTP4A1 is trimeric in the crystalline state and in solution. 83 Previous studies suggest that trimer formation is essential for PTP4A1-mediated cell growth and migration. Moreover, the interface responsible for PTP4A1 homotrimerization is shared by the other PTP4A family members.…”
Section: Ptp4amentioning
confidence: 99%
“…This stimulated a computer-based virtual search for small molecules capable of disrupting PTP4A trimerization. 53,83 Biochemical and structural analyses identified compound 43, which binds to the PTP4A1 trimer interface and blocks trimerization of PTP4A1, PTP4A2, and PTP4A3. 53 Compound 43 also specifically abrogated the PTP4A1-induced cell proliferation and migration through attenuation of both ERK1/2 and AKT activity.…”
Section: Ptp4amentioning
confidence: 99%